Comprehensive screening of chymotrypsin C (CTRC) gene in tropical calcific pancreatitis identifies novel variants. Issue 11 (12th May 2012) - Paliwal, Sumit; Bhaskar, Seema; Mani, K Radha; Reddy, D Nageshwar; Rao, G Venkat; Singh, Shivaram Prasad; Thomas, Varghese; Chandak, Giriraj Ratan
Abstract : Objective: In a previous study, the authors have shown that rather than variants in trypsinogen gene(s), mutations in pancreatic secretory trypsin inhibitor (encoded by SPINK1 ) and cathepsin B ( CTSB ) are associated with tropical calcific pancreatitis (TCP). Recently, chymotrypsin C ( CTRC ) variants that diminish its activity or secretion were found to predict susceptibility to chronic pancreatitis (CP). The authors analysed CTRC variants in a large, ethnically matched case-control TCP cohort. Design: The authors sequenced all eight exons and flanking regions in CTRC in 584 CP patients (497 TCP, 87 idiopathic CP) and 598 normal subjects and analysed the significance of association using χ 2 test. The authors also investigated interaction of CTRC variants with p.N34S SPINK1 and p.L26V CTSB mutations. Results: The authors identified 14 variants in CTRC, of which non-synonymous variants were detected in 71/584 CP patients (12.2%) and 22/598 controls (3.7%; OR 3.62, 95% CI 2.21 to 5.93; p=6.2×10 −8 ). Rather than the commonly reported p.K247_R254del variant in Caucasians, p.V235I was the most common mutation in Indian CP patients (28/575 (4.9%); OR 7.60, 95% CI 2.52 to 25.71; p=1.01×10 −5 ). Another pathogenic variant, p.A73T was identified in 3.1% (18/584) patients compared with 0.3% (2/598) in controls (OR=9.48, 95% CI 2.19 to 41.03, p=2.5×10 −4 ). The authors also observed significant association for the synonymous variant c.180C>T (p.(=)) with CP (OR 2.71, 95% CI 1.79 to 4.12, p=5.3×10 −7 ). Two novel nonsense mutations, p.G242AfsX9 and p.W113X were also identified exclusively in CP patients. No interaction between CTRC variants and p.N34S SPINK1 or p.L26V CTSB mutations was observed. Conclusion: This study on a large cohort of TCP patients provides evidence of allelic heterogeneity and confirms that CTRC variants play a significant role in its pathogenesis.